2012
DOI: 10.1002/path.3988
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma‐derived growth factor regulates breast cancer cell invasion by modulating epithelial–mesenchymal transition

Abstract: Hepatoma-derived growth factor (HDGF) participates in tumourigenesis but its role in breast cancer is unclear. We set out to elucidate the expression profile and function of HDGF during breast carcinogenesis. Immunoblot and immunohistochemical studies revealed elevated HDGF expression in human breast cancer cell lines and tissues. Nuclear HDGF labelling index was positively correlated with tumour grade, stage and proliferation index, but negatively correlated with survival rate in breast cancer patients. HDGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…Down-regulation of HDGF participates in miRNAs-induced suppression of migration and invasion on several cancer cells Guo et al, 2014a), and induces relapse of various cancer cells . Moreover, previous studies had shown that HDGF overexpression promoted epithelial-mesenchymal transition (Chen et al, 2012a;Tsai et al, 2013) and affected cell metastasis processes via mitogen-activated protein kinase signaling pathways (Mao et al, 2008) or a novel HDGF-disintegrin and metalloproteinase-9 pathway , thereby promoting the invasion and metastasis in several cancer cells. In addition, combining the anti-HDGF antibody with anti-VEGF antibody might enhance their antiangiogenic activities (Ren et al, 2009).…”
Section: The Funnel Prognostic Role Of Hepatoma-derived Growth Factormentioning
confidence: 98%
See 3 more Smart Citations
“…Down-regulation of HDGF participates in miRNAs-induced suppression of migration and invasion on several cancer cells Guo et al, 2014a), and induces relapse of various cancer cells . Moreover, previous studies had shown that HDGF overexpression promoted epithelial-mesenchymal transition (Chen et al, 2012a;Tsai et al, 2013) and affected cell metastasis processes via mitogen-activated protein kinase signaling pathways (Mao et al, 2008) or a novel HDGF-disintegrin and metalloproteinase-9 pathway , thereby promoting the invasion and metastasis in several cancer cells. In addition, combining the anti-HDGF antibody with anti-VEGF antibody might enhance their antiangiogenic activities (Ren et al, 2009).…”
Section: The Funnel Prognostic Role Of Hepatoma-derived Growth Factormentioning
confidence: 98%
“…The following articles were also excluded: three duplicated publications (Zhou et al, 2007b;Zhou et al, 2010a;Yang et al, 2014); three without data for HR and 95%CI calculations and adequate contact with the investigators could not be established (Natrajan et al, 2006;Mao et al, 2008;Hanada et al, 2013); two with a sample size<50 (Hsu et al, 2012;Tao et al, 2014); two in which HDGF expression was not detected by IHC methods (Savola et al, 2009;Zhang et al, 2010); three uncorrelated. Finally, 26 cohort studies were found eligible for the meta-analysis (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Lin et al, 2012;Han et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Zhang et al, 2014), containing 32 datasets (29 datasets for OS; 17 datasets for DFS) were qualified to the standard of the meta-analysis. The main characteristics of the selected studies were summari...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…HDGF has also been recognized as an important prognostic marker that HDGF overexpression was correlated with advanced stages and poor survival outcome in several types of cancers including liver cancer (13) and esophageal carcinoma (14). Furthermore, we have recently shown that HDGF overexpression promoted epithelial-to-mesenchymal transition (EMT) by E-cadherin downregulation and vimentin upregulation, thereby promoting the invasion and metastasis in breast cancer cell (15). However, the upstream molecules or signaling mechanisms that modulate HDGF expression and therefore affect cancer progression remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%